Transport Asset Management Plan Guideline for Climate Resilience and Road Safety (Phase I) for the Municipality of Ulaanbaatar - World Bank (Washington, DC: World Bank, 2022)
This is the first iteration of a Transport Asset Management Planning (TAMP) Guideline for Ulaanbaatar. This TAMP Guideline I guides the Municipality of Ulaanbaatar (MUB) to move away from its conventional reactive decision-making approach and adopt a systematic, evidence- and risk-based approach in maintaining its road assets. The reactive way of doing business, which postpones repair activities until major deterioration occurs, is no longer sustainable. It is too expensive, and it erodes the value of important and costly road assets. As the costs of operating and repairing roads continue to increase, it has become more difficult for the MUB to meet the demands of an aging and expanding infrastructure while dealing with public expectations to provide the same level of service. This TAMP Guideline can therefore serve as a medium- and long-term tactical guide for MUB to plan for repair and maintenance of its transport assets to provide good quality road network to UB’s citizens while optimizing the use of its scarce financial resources for maintenance and repairs. The TAMP incorporates two key risks that strain the performance and safety of UB’s road network: climate risks (particularly urban flooding) and road safety risks.